IMPROVING STUDENTS WRITING SHORT STORIES THROUGH WATTPAD APPLICATION - Yulandari, Evi Safitri; Paris, Atika Salman; Sukisno, Sukisno (Jurnal Ilmiah Global Education, 2023)
This research aims to determine the role of the Wattpad application in honing the ability to write short stories for second grade students of SMAN 3 Praya. This type of research uses qualitative research with descriptive methods. The subjects of this research were students of class XI IPA 2 at SMA Negeri 3 Praya in the academic year 2022/2023, consisting of 13 boys and 18 girls. The researcher uses observation sheets, interview, and documentation to collect the data. The results of this research show that the Wattpad application makes it easy to train readers' imaginations and provide ideas that can be developed more broadly, Wattpad trains them to empathize, so they can pour various emotions into their stories and teach students how to write good and correct stories, so that there is a desire to be able to write for students after reading several stories contained in the Wattpad application. The conclusion from the research was the Wattpad application can help students to improve students' writing short stories because in the Wattpad application they learn to make good stories, use the right words and build emotions in a story.